A novel implementation of IEDG-based DDM for solving electromagnetic scattering from large and complex PEC objects. Issue 1 (2nd January 2018) - Han, Kui; Nie, Zaiping; Jiang, Ming; Chen, Yongpin; Hu, Jun
ABSTRACT: A novel implementation of the integral equation discontinuous Galerkin (IEDG)-based domain decomposition method (DDM), named as the IEDG-DDM, is developed for the efficient analysis of electromagnetic scattering from large and complex perfect electrically conducting (PEC) objects. Due to the nature of the IEDG scheme, the proposed DDM is nonconformal and nonoverlapping. Therefore, each sub-domain can be meshed independently according to the local geometrical feature, leading to a flexible discretization and a minimum number of unknowns. Different from the IEDG formulation in the skew-symmetric interior penalty DDM, the current continuity at the sub-domain boundaries is enforced through a properly defined interior penalty term, where the error energy from the electric potential is minimized. Consequently, the troublesome implementation of the stabilization term, which requires complex geometrical operations to find the intersection of edges in a nonconformal mesh, can be totally avoided. The proposed DDM results in an effective nonoverlapping domain decomposition preconditioner and a fast convergence of Krylov sub-space iterative solvers can be achieved. This method can be easily applied to curved sub-domain boundaries or curvilinear discretizations. Numerical examples are presented to demonstrate the accuracy and efficiency of the proposed method.